Flipping Fair Faces

You flip a fair coin repeatedly until either four consecutive heads ( H ) (H) or six consecutive tails ( T ) (T) occur. The probability that the sequence H H H H HHHH occurs before the sequence T T T T T T TTTTTT can be expressed as a b \frac{a}{b} , where a a and b b are positive coprime integers. What is a + b a + b ?


The answer is 47.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Abhishek Sinha
Jun 25, 2017

Let us denote the event of obtaining four consecutive heads before six consecutive tails by E E . Now, the following equations must be satisfied P ( E 1st toss is H ) = 1 2 3 + ( 1 1 2 3 ) P ( E 1st toss is T ) P ( E 1st toss is T ) = ( 1 1 2 5 ) P ( E 1st toss is H ) \mathbb{P}(E| \textrm{ 1st toss is H })= \frac{1}{2^3}+ (1-\frac{1}{2^3})\mathbb{P}(E| \textrm{ 1st toss is T})\\ \mathbb{P}(E| \textrm{ 1st toss is T })= (1-\frac{1}{2^5})\mathbb{P}(E| \textrm{ 1st toss is H }) The first equation may be derived by considering the fact that, when the result of the first toss is H H , the event E E occurs when the next 3 3 consecutive tosses are H H (with probability 1 2 3 \frac{1}{2^3} ), or there is a T T before three consecutive H H occurs (with probability ( 1 1 2 3 ) P ( E 1st toss is T ) (1-\frac{1}{2^3})\mathbb{P}(E| \textrm{ 1st toss is T}) ). The second equation may also be argued similarly.

Solving the above equations, we have P ( E 1st toss is H ) = 32 39 , P ( E 1st toss is T ) = 31 39 . \mathbb{P}(E| \textrm{ 1st toss is H})= \frac{32}{39}, \mathbb{P}(E| \textrm{ 1st toss is T}) =\frac{31}{39}. Hence, P ( E ) = 1 2 P ( E 1st toss is H ) + 1 2 P ( E 1st toss is T ) = 21 26 . \mathbb{P}(E)= \frac{1}{2}\mathbb{P}(E| \textrm{ 1st toss is H})+ \frac{1}{2}\mathbb{P}(E| \textrm{ 1st toss is T})=\frac{21}{26}. \blacksquare

Mark Hennings
Jun 25, 2017

Let p j p_j , for j = 1 , 2 , 3 , 1 , 2 , 3 , 4 , 5 j=1,2,3,-1,-2,-3,-4,-5 be the probability that H H H H HHHH occurs before T T T T T T T TTTTTTT , given that your current streak is of j j Heads. Note that a negative streak of Heads represents a streak of Tails, so that p 3 p_{-3} is the probability that H H H H HHHH occurs before T T T T T T TTTTTT given that your current streak is T T T TTT .

Conditional probability considerations tell us that p 3 = 1 2 + 1 2 p 1 p 2 = 1 2 p 3 + 1 2 p 1 p 1 = 1 2 p 2 + 1 2 p 1 p 1 = 1 2 p 2 + 1 2 p 1 p 2 = 1 2 p 3 + 1 2 p 1 p 3 = 1 2 p 4 + 1 2 p 1 p 4 = 1 2 p 5 + 1 2 p 1 p 5 = 1 2 p 1 \begin{aligned} p_3 & = \tfrac12 + \tfrac12p_{-1} \\ p_2 & = \tfrac12p_3 + \tfrac12p_{-1} \\ p_1 & = \tfrac12p_2 + \tfrac12p_{-1} \\ p_{-1} & = \tfrac12p_{-2} + \tfrac12p_1 \\ p_{-2} & = \tfrac12p_{-3} + \tfrac12p_1 \\ p_{-3} & = \tfrac12p_{-4} + \tfrac12p_1 \\ p_{-4} & = \tfrac12p_{-5} + \tfrac12p_1 \\ p_{-5} & = \tfrac12p_1 \end{aligned} so that p 1 = 1 8 + 7 8 p 1 p 2 = 1 4 + 3 4 p 1 p 3 = 1 2 + 1 2 p 1 p_1 \; = \; \tfrac18 + \tfrac78p_{-1} \hspace{1cm} p_2 \; = \; \tfrac14 + \tfrac34p_{-1} \hspace{1cm} p_3 \; = \; \tfrac12 + \tfrac12p_{-1} and p 1 = 31 32 p 1 p 2 = 15 16 p 1 p 3 = 7 8 p 1 p 4 = 3 4 p 1 p 5 = 1 2 p 1 p_{-1} \; = \; \tfrac{31}{32}p_1 \hspace{1cm} p_{-2} \; = \; \tfrac{15}{16}p_1 \hspace{1cm} p_{-3} \; = \; \tfrac78p_1 \hspace{1cm} p_{-4} \; =\; \tfrac34p_1 \hspace{1cm} p_{-5} \; =\; \tfrac12p_1 Solving the simultaneous equations for p 1 p_1 and p 1 p_{-1} given here, we deduce that p 1 = 32 39 p 1 = 31 39 p_1 \; =\; \tfrac{32}{39} \hspace{2cm} p_{_1} \; = \; \tfrac{31}{39} and so the overall probability of H H H H HHHH occurring before T T T T T T TTTTTT is 1 2 ( p 1 + p 1 ) = 21 26 \tfrac12(p_1 + p_{-1}) \; = \; \boxed{\tfrac{21}{26}}

Could you add this too p0 = 1/2(p1 + p-1) to make it more complete, basically saying the first toss is half way on either side. Your solution makes the problem look very elementary, thanks for the solution.

Siva Bathula - 3 years, 11 months ago

Log in to reply

Without defining p 0 p_0 , I already do this in the last line of my proof.

Mark Hennings - 3 years, 11 months ago

Log in to reply

Yeah, seems ok.

Siva Bathula - 3 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...